Ozonated Aloe Vera: A Novel Topical Agent for Improved Wound Healing and Reduced Scar Formation on TGF-β Modulation Invivo Study - Ahsanu Taqwim Hidayat; Parish Budiono (HM Publisher, 2025)
Background: Chronic wounds and impaired wound healing represent a significant healthcare burden. Aloe vera has been recognized for its therapeutic potential in wound healing, and the combination with ozone, and ozonated aloe vera, may offer synergistic effects. This study investigated the effects of ozonated aloe vera oil on wound healing and scar formation, focusing on TGF-β modulation in a rat model. Methods: Full-thickness skin defects were created on 50 Sprague Dawley rats, which were randomly divided into five groups: (1) control (untreated), (2) aloe vera oil, (3) ozonated aloe vera oil (600 mg/ml ozone), (4) ozonated aloe vera oil (1200 mg/ml ozone), and (5) ozonated aloe vera oil (1800 mg/ml ozone). Wound healing was assessed macroscopically by measuring wound area reduction and microscopically by evaluating TGF-β expression through immunohistochemical staining on days 3, 7, and 14. Results: Ozonated aloe vera oil significantly accelerated wound healing compared to the control and aloe vera oil alone groups (p < 0.05). The highest ozone concentration (1800 mg/ml) showed the most rapid wound closure and the lowest TGF-β expression on day 14 (p < 0.05). Histological analysis revealed enhanced collagen organization and reduced inflammatory cell infiltration in ozonated aloe vera oil treated wounds. Conclusion: Ozonated aloe vera oil effectively promotes wound healing and reduces scar formation in a rat model. The modulation of TGF-β signaling plays a crucial role in these effects. Ozonated aloe vera oil holds promise as a novel topical agent for improved wound management.